THE DEVELOPMENT OF A SUPPLEMENTARY COURSE ENGLISH FOR CAREER TO IMPROVE SPEAKING AND ANALYTICAL THINKING ABILITIES OF GRADE 9 STUDENTS USING ACTIVITIY-BASED LEARNING WITH CONCEPT MAPPING - Wongsapan, Salisa; Sitthipon Art-in, Sitthipon Art-in (Journal for Developing the Social and Community, 2023)
The research study purpose were: 1) develop the Supplementary course English for Career to improve speaking and analytical thinking of grade 9 students using Activity-Based Learning with Concept Mapping 2) effect of using the Supplementary course English for Career: 2.1) The result of speaking ability 2.2) The result of analytical thinking. The target group of 27 participants were selected from grade 9/2 students in the first semester of the 2021 year at Naphiangsawangwitthayanukun School, the Sakonnakhon Primary Education Service Area Office 1. The study was Research and Development. The instruments of the study were 1) a questionnaire which was in the checklist inquiring the demands for the develop the Supplementary course 2) an interview investigating opinions to the importance and essential elements for develop the Supplementary course 3) an evaluation assessing the structure of curriculum 4) the curriculum of Supplementary course 5) lesson plans 6) speaking test 7) analytical thinking test and 8) a questionnaire which was in the checklist inquiring about the adopting of the curriculum. The data were analyzed using mean (), standard deviation (S.D.) and percentage (%) The results of the study were as follow The result of the develop the Supplementary course English for Career to improve speaking and analytical thinking of grade 9 students consisting of 10 elements; 1) principle 2) the objectives of the curriculum 3) learning results 4) a subject description 5) guidelines for learning management 6) teaching aids 7) evaluations 8) the curricular structure 9) units and 10) lesson plan, evaluated by the experts suggested that the curriculum is the highest corresponding (=4.72, S.D.=0.09) 2. The result of adopting the develop the Supplementary course English for Career were the following: 2.1) The students had average result of speaking at 19.78 or 79.11%. There were 26 students meeting the criteria 96.30% of all participants which was higher than the determined norm. 2.2) The students had average score of analytical thinking at 23.11 or 85.60%. There were 21 students meeting the criteria 77.78% of all participants which was higher than the determined standard.